Memory Assessment of the Organic Solvents Exposed among Cambodian Workers in a Toy Manufacturing Factory - Atenta, Keremas; Thetkathuek, Anamai; Phatrabuddha, Nantaporn (Princess of Naradhiwas University Journal, 2019)
The objectives of this study were to assess the memory of Cambodian workers who were exposed to organic solvents from color painting in a toy manufacturing factory, and compare the memory between an exposed and a control group. The sample size of each group was 103 workers. Data were collected using interview form and the Psychology Experiment Building Language (PEBL) computer program for digit span forward and backward memory scores for memory impairment evaluation. Data were analyzed using independent samples t-test. The results showed that both Cambodian worker groups had similar characteristics. The analysis of memory scores from the digit span forward and backward test between exposed and control group revealed that the exposed group had less memory scores of both digit span backward tests. The digit span forward and backward memory scores of exposed group were significantly different from control group at less than 0.01. The t-test score equal to -2.842 (0.756, - 0.137) and -3.221 (-0.736, - 0.177), respectively. The data from this research can be used as a guideline for employee health care in order to prevent memory defects from work.